Pengaruh Tingkat Pengangguran, Kebutuhan Pangan, Peningkatan Gizi, Dan Peningkatan Pendapatan Per Kapita Terhadap Kawasan Rumah Pangan Lestari (KRPL) - Supardi Supardi; Nurshadrina Kartika Sari (RELASI : JURNAL EKONOMI, 2018)
This study aims to analyze the effect of unemployment rate, food demand, nutrition improvement and income increase per capita after applying Sustainable Food House (KRPL) in Jember Regency. Analysis tool used Multiple Regression Analysis is the number of independent variables used to predict variables depend on more than one. The research design used is associative design, ie to analyze the relationship between one variable with other variables or how a variable affects other variables. The writer uses case study with quantitative approach while the unit of analysis in this research is the influence of Unemployment rate, Food Needs, Nutrition Improvement, and Increase Revenue per Capita to Area Sustainable Food House (KRPL). The sampling method used is the census method, which is a comprehensive sampling of 3 villages with a 3-year study period from 2014 to 2016. Analytical techniques are multiple regression analysis, F test and t test. Keywords: unemployment, food, nutrition, income and krpl.